2021
DOI: 10.2478/pcssr-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Multilateral teaching in physical education improves resilience and self-efficacy in adolescents and could help reduce bullying behaviors

Abstract: Youth with higher levels of resilience and self-efficacy are less likely to engage in aggressive behaviors or be victims of bullying. Previous anti-bullying approaches have often achieved no reduction in bullying behavior. Thus, the aim of this study was to examine the effect of 12 weeks of extracurricular multilateral teaching on the risk for students (aged 14–16 years) to be involved in bullying. Sixty male students were allocated to an experimental group (n = 30) that performed psychoeducational activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…First, an inverse and significant correlation was found between the E-AEM scale scores and both dimensions of the ECIP-Q questionnaire of average character in the abuser, which means that the higher the score on the motor self-efficacy scale, the lower the score on this dimension, establishing that the abuser is less likely to commit actions of this style if he/she has higher motor self-efficacy. In this sense, authors who have explored the behaviors of students in relation to motor self-efficacy have found results in line with what has been described, establishing that a better motor self-efficacy could be related to a better regulation of behavior and an increase in empathy towards peers, decreasing this type of disruptive behavior ( Greco, 2021 ; Arcila-Arango et al, 2022 ). Other studies have found that a higher level of self-efficacy can reduce the likelihood of students being victimized by cyberbullying.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…First, an inverse and significant correlation was found between the E-AEM scale scores and both dimensions of the ECIP-Q questionnaire of average character in the abuser, which means that the higher the score on the motor self-efficacy scale, the lower the score on this dimension, establishing that the abuser is less likely to commit actions of this style if he/she has higher motor self-efficacy. In this sense, authors who have explored the behaviors of students in relation to motor self-efficacy have found results in line with what has been described, establishing that a better motor self-efficacy could be related to a better regulation of behavior and an increase in empathy towards peers, decreasing this type of disruptive behavior ( Greco, 2021 ; Arcila-Arango et al, 2022 ). Other studies have found that a higher level of self-efficacy can reduce the likelihood of students being victimized by cyberbullying.…”
Section: Discussionsupporting
confidence: 62%
“…With the aim of developing a tool that allows the measurement of this construct and enables comparison with other variables, the (E-AEM), a scale composed of 10 items, was developed ( Hernández-Álvarez et al, 2011 ). Self-efficacy has been studied as a determining factor in academic performance, finding positive correlations in fields such as mathematics and language ( Hayat et al, 2020 ; Luo et al, 2023 ), in the field of physical activity, specifically in motor self-efficacy, it has been determined that the perception of self-efficacy acts as a mediator in the regulation of behavior, directly associated with the practice of physical activity in youth and, therefore, with the appearance of aggressive or undesired behaviors ( Welk and Schaben, 2004 ; Greco, 2021 ). Authors who have studied the possible relationships between physical activity and behavior have found that physical activity is an ideal and effective means for the transmission of prosocial and positive values, while those who practice physical activity on a recurrent basis are less likely to develop problematic behaviors, including a lower probability of bullying and cyberbullying ( Portolés Ariño and González Fernández, 2015 ; González et al, 2016 ; Arcila-Arango et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“… 25 Arufe-Giráldez et al found that sedentary students are more prone to encounter relational bullying. 24 In addition, according to Greco, 26 psychoeducational activities combined with physical activity and team sports may promote resilience and self-efficacy in male adolescents and reduce aggression and bullying victimization in PE. Furthermore, Jachyra 27 reported that non-dominant individuals often faced regular bullying due to their capabilities in physical movement.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies examined the relationship between bullying behaviors and physical movement factors (such as physical activity, sedentary behavior, physical exercise, and sports competence). [24][25][26][27][28] Participation in physical activity was associated with verbal and physical victimization, 24 as well as cyber-victimization. 25 Arufe-Giráldez et al found that sedentary students are more prone to encounter relational bullying.…”
Section: Physical Movement Factorsmentioning
confidence: 99%
“…Later, the SEQ-C was tested with 596 Belgian students aged 12–19 years (Muris, 2002 ). Several studies have confirmed the high reliability, stability, and construct validity of the SEQ-C with the general adolescent population (Andretta & McKay, 2020 ; Greco, 2021 ; Habibi et al, 2014 ; Minter & Pritzker, 2017 ; Tan & Chellappan, 2018 ) and DHH adolescents (Bolívar-Cruz et al, 2018 ; Evans, 2021 ). In the present study, the Cronbach’s α for all the three subscales was above 0.81 for both DHH and hearing students.…”
Section: Methodsmentioning
confidence: 91%